28 years later [videorecording (DVD)] - Garland, Alex, 1970-; Comer, Jodie, 1993-; Taylor-Johnson, Aaron, 1990-; O'Connell, Jack, 1990-; Williams, Alfie; Lewis-Parry, Chi; Ryding, Edvin; Fulford, Christopher; Fiennes, Ralph; Gonet, Stella; Laird, Emma; Kellyman, Erin; et al. (Sony Pictures Home Entertainment, 2025)
"It's been almost three decades since the rage virus escaped from a biological weapons laboratory. Still living in a ruthlessly enforced quarantine, some have found ways to exist amid the infected. One such group of survivors lives on a small island connected to the mainland by a single, heavily defended causeway. When one of them decides to venture into the dark heart of the mainland, he soon discovers a mutation that has spread to not only the infected, but other survivors as well."--